Policy strategies for climate-resilient infrastructure in climate change adaptation: jurisdictional comparison between Chile and Indonesia - Maskun Maskun; Al Mukarramah Nurul Habaib; Angi Josse Charmario Wara (E3S Web of Conferences, 2023)
The impact of climatic change such as extreme weather events and sea level rise have resulted in a greater burden for countries surrounded by waters including Indonesia as an archipelagic state and Chile as a coastal state to adapt to climate-related disasters and building resilience by developing climate-resilient infrastructure. This article is purposed to analyze legal regulation to strategize preparedness in climate adaptation policy by incorporating climate-resilient infrastructure. This article utilizes jurisdictional-based comparative legal methods as a part of normative legal research, with statutory approach through laws and regulations as its primary data, with country practices obtained through literary sources used as secondary data. The result reveals that there are two strategies needed to be taken by countries for climate adaptation policy: 1) Policy initiation and formulation based on climate change risk mapping by considering potential financial cost, appearing social problems and environmental impact; 2) Policy enactment through legal instruments mandating state to provide climate-resilient infrastructure to adapt to climate change. Chile demonstrates best practice in policy formulation strategies through initiation of ARClim and enacting climate change legislation in 2022, compared to Indonesia with no existing climate change legislation and national climate risk mapping. In conclusion, this research implies that countries prone to climate change impacts including Indonesia shall urgently initiate, formulate and enact policies incorporating climate-resilient infrastructure through the proposed strategies.